The assessment algorithm of technological feasibility of SOx scrubber installation - Panasiuk, Irina; Lebedevas, Sergejus; Čerka, Jonas (Transport, 2018)
The problematics of installation of sulphur oxides (SOx) scrubber becomes much relevant for today due to the new Annex VI of MARPOL 73/78 requirements, which sets 0.1% SOx limits by 2015 in Emission Control Area (ECA) and globally to 0.5% in 2020. The research in this field becomes more significant for ship-owners. SOx scrubber is most promising alternative because of lower operating costs and suitability to existing ships. Despite the fact that exhausts gas scrubbing is a common and proven technology on land, the conditions on ships differ significantly and still there are not enough practical knowledge of installation of mentioned equipment. In addition, speaking about existing ships there are some limitation factors of SOx scrubber installation on-board, which will be discussed in the paper. Taking into account the size and mass of the SOx scrubber, it can be assumed that the recalculation of ship stability will be required for most ships. Therefore, the most important task for equipment designers is selection of scrubber system location with the minimum impact on ship stability and identification of necessary changes (deadweight, additional space, etc.) in accordance with ship safety requirements. For this reason, the research was carried-out in order to create the algorithm of ship stability assessment and selection of optimal scrubber location on-board. First published online 29 March 2016